An economic analysis of the Cattlemen's Beef Promotion and Research Board demand-enhancing programmes. Issue 4 (20th January 2016) - Kaiser, Harry M.
ABSTRACT: The research reported here addressed two objectives. The first objective was to measure the overall impact of the Cattlemen's Beef Board as well as eight-specific advertising, promotion and research activities on US beef demand. The second objective was to compute marginal benefit–cost ratios (BCRs) for the eight individual checkoff activities and for the overall programme. The results indicated that Cattlemen's Beef Board's Promotion activities increased total domestic beef demand by 15.7 billion pounds in total, or 2.1 billion pounds per year between 2006 and 2014. Collectively, the overall marginal BCR for all Cattlemen's Beef Board activities was $11.20.